Neural responses to food cues in middle to older aged adults: a scoping review of fMRI studies. Issue 3 (15th November 2020) - Bennett, Christie; Burrows, Tracy; Pursey, Kirrilly; Poudel, Govinda; Ng, Ker Wei; Nguo, Kay; Walker, Karen; Porter, Judi
Abstract: Aim: Understanding neural responses through functional magnetic resonance imaging (fMRI) to food and food cues in middle‐older adults may lead to better treatment options to address the growing issue of malnutrition. This scoping review aimed to determine the extent, range and nature of research using fMRI, related to reward‐based regions, in response to food cues in middle to older aged adults (50 years and over). Methods: The following databases were systematically searched in July 2019: CINAHL, CENTRAL, Embase, Dissertations and Theses, Ovid Medline, PsycINFO, PsycEXTRA, Scopus and Web of Science. Studies were eligible for inclusion if participants had a mean or median age ≥50 years, utilised and reported outcomes of either a food cue task‐related fMRI methodology or resting‐state fMRI. Data from included studies were charted, and synthesised narratively. Results: Twenty‐two studies were included. Eighteen studies utilised a task‐related design to measure neural activation, two studies measured resting state neural connectivity only and an additional two studies measured both. The fMRI scanning paradigms, food cue tools and procedure of presentation varied markedly. Four studies compared the neural responses to food between younger and older adults, providing no consensus on neural age‐related changes to food cues; two studies utilised longitudinal scans. Conclusion: This review identified significant extent, range and nature in the approaches used to assess neuronal activity in response to food cues in adults aged 50 years and over. Future studies are needed to understand the age‐related appetite changes whilst considering personal preferences for food cues.